Islam dan Negara dalam Kemelut Pasca Kemerdekaan: Telaah Historiografi Karya Bernard Johan Boland, Pergumulan Islam di Indonesia 1945-1970 - Dirga Fawakih (Jurnal Tamaddun, 2023)
In the current of Indonesian history, Islam is an important element that is inseparable in the formation and development of the nation. Islam is more than just a value that governs the social-religious life of its adherents, it also permeates various aspects of state life, such as social, economic, cultural, and political. Although a country with an Islam majority, Muslims must be intertwined in a crucial discourse in the early days of the nation's formation. Bernard Johan Boland became a foreign scholar who also noted how Muslims contended for taking an ideal position in the formation of the nation. Through his work, The Struggle of Islam in Indonesia 1945 – 1970, Boland also explored the treasures of post-independence Islamic historiography which at that time few people paid attention to.  Boland's work is considered a continuation of Harry J. Benda's work, The Crescent and the Rising Sun, which tried to see Islam as a movement that continued to seek an ideal position in the formation and building of the nation. This article attempts to review and provide historiographical review notes of B.J. Boland's work using the comparison method. The author seeks to provide a historiographical review note to look at the perspectives, arguments, and sources used by Boland in his book and make comparisons with works published by contemporaries or predecessors.